(untitled) (Research, Society and Development, 2020)
The challenge of maintaining the vitality of a pulp exposed accidentally or through caries has been the subject of investigations for many years. The use of calcium hydroxide as capping material in the dental clinic is a custom and several studies prove its excellent result. However, a new caping material is suggested, the dentin adhesive, becoming one of the most controversial issues in dentistry. The objective was to evaluate, through a literature review, the comparison of these techniques in relation to effectiveness. The keywords “pulp capping”, “calcium hydroxide” and “hybridization” were used in the PubMed and BVS databases. The references that dealt with the subjects related to the proposed theme were chosen, published during the last 20 years. The dental adhesive would produce a hybrid layer that would provide an effective and permanent seal against bacterial invasion, promoting pulp healing, being indicated for pulp capping procedures. Just as calcium hydroxide was challenged regarding its inability to promote a permanent seal against bacterial invasion, the integrity and durability of adhesion achieved with dentin adhesives, can be questioned. Despite boasting promise and offering a different treatment possible in the future, the lack of documentation of long-term clinical successes for performing pulp capping with adhesive systems in controlled clinical experiments must be examined against the literature that demonstrates success with use calcium hydroxide of 75-90% for more than 12 years.